Subversion and Gender Performativity in the Film Clueless (1995): An Analysis Based on Judith Butler's Theory - Lenni Herawati Sirait; Sinambela , Berlian Hasian Keyla; Fadillah, Teuku Muhammad Raihan; Rangkuti, Rahmadsyah (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study explores the representation and subversion of gender norms in the film Clueless (1995), directed by Amy Heckerling, using Judith Butler's theory of gender performativity. The film blends teen humor with social critique on class, identity, and gender, illustrating how gender identities are constructed and performed through characters such as Cher, Tai, and Christian. By analyzing these characters’ performances, the study reveals how gender is not a fixed identity but a dynamic social construct shaped by repeated actions and societal expectations. Fashion plays a pivotal role in this performativity, highlighting gender as both a stylized performance and a marker of individuality. Additionally, the subversion of traditional masculinity and the critique of gender norms through humor offer alternative portrayals of gender roles. The study concludes that Clueless challenges and redefines gender identities, reinforcing the idea that gender is fluid and performative, thus providing a powerful tool for critiquing and reshaping societal norms.